A Theological Reflection on Children-at-Risk. (July 2016) - Willmer, Haddon; Prevette, Bill
This essay concentrates on the term 'children-at-risk' taken on its own. However much risk and need are intertwined in practice, they are distinguishable as concepts. 'Children-at-risk' is not a virtual synonym of 'children in need'. It is theologically suggestive and worth exploring because faith is always seeking understanding. All children are at risk in some way. Risks take various forms, each calling for an appropriate response. All risks are components of the ultimate risk of being human, of falling short of the glory of God, of failing to be, to become and to persist in being, truly human, as measured in the fullness of Christ. Thus all risks have theological significance, unless God is denied totally, or restricted and stifled in a religious cave. God, Father, Son and Holy Spirit share the risk of being human mysteriously, really and unreservedly. This understanding of risk comes to us from our lived experience and from the revelation of God in Christ, as witnessed in the Scriptures. Action for children-at-risk and in need is obedience to the core of the Gospel in Jesus Christ. Engaged concern for children-at-risk brings us into practical difficulties, which are also theological.